PD-1/PD-L1 Axis in Lung Cancer. Issue 1 (January 2018) - Santini, Fernando C.; Hellmann, Matthew D.
Abstract : Abstract: Cancer immunotherapies have revolutionized the treatment of non–small cell lung cancer. Yet, only a small subset of patients will benefit from PD-1 or PD-L1 blockade. PD-L1 tumor cell expression is the only approved biomarker at present. Tumor mutational burden and other emerging biomarkers should improve patient selection. Combination therapy approaches with chemotherapy or cytotoxic T-lymphocyte-associated protein 4 blockade may increase the proportion of patients who benefit from immunotherapy. Although use of immunotherapy in lung cancers with targetable oncogenes has not been particularly successful, the benefit of PD-(L)1 inhibitors in early-stage disease is emerging. This review briefly describes the evolution of the clinical development and future directions of PD-(L)1 blockade in patients with lung cancers.